FE’L SO‘Z TURKUMINI O‘RGANISH METODIKASI - Atiyazov, S.J. (SCIENCE and SOCIETY, 2025)
In this article, the importance of the method of teaching verbs and how to teach this area is discussed in detail. In addition, it was discussed about the presentation of practical examples and exercises on the method of teaching verbs using interactive methods.